Socialization the Influence of Human Resource Competencies on Work Productivity at PT. Intidragon Suryatama Mojokerto - Yulaidin, Totok (PT FORMOSA CENDEKIA GLOBAL, 2024)
Currently, competition in the industrial is getting tougher. This makes the industry have to improve the effectiveness and efficiency in carrying out the production process. In the footwear industry, which is a labor-intensive industry that employs a lot of workers, the level of employee ability and competency is very important. n this community service activity, we directly conducted socialization to employees of PT. Intidragon Suryatama especially for the Group Head level and above. This socialization is intended so that they understand how much impact employee competence has on work productivity. In this socialization, it was also practiced directly how to measure employee competence using a performance assessment form. So that it is hoped that with this assessment, the company will be able to measure the level of competence of its employees.